Melatonin protects sperm cells of Capoeta trutta from toxicity of titanium dioxide nanoparticles - Ozgur, Mustafa Erkan; Ulu, Ahmet; Noma, Samir Abbas Ali; Ozcan, Imren; Balcioglu, Sevgi; Ates, Burhan; Koytepe, Suleyman (Springer Heidelberg, 2020)
In this study, it was aimed to determine the protective effects of melatonin (0.01, 0.1, and 1 mM) against 10 mg/L titanium dioxide nanoparticles (TiO2-NPs) on kinematic and oxidative indices in the sperm cells of Capoeta trutta. Therefore, TiO2 nanoparticles were synthesized primarily within the scope of the study. The synthesized nanoparticles were characterized by structurally different techniques. Then, melatonin and TiO2 were applied to Capoeta trutta sperm cells by in vitro. According to our data, all doses of melatonin showed protective effects on all velocities of sperm cells such as the straight line velocity (VSL), the curvilinear velocity (VCL), and the angular path velocity (VAP) against TiO2-NPs, while 0.1 and 1 mM doses of melatonin improved the VSL value. Although TiO2-NPs increased total glutathione (tGSH), malondialdehyde (MDA) lipid peroxidation, and superoxide dismutase (SOD) compared to the control group, there were positive treatment effects for all doses of melatonin on antioxidant capacity of sperm cells. At the end of this research, it is suggested that over 0.1 mM dose of melatonin improves the velocity of sperm cells and it plays a protective role against the toxic effects of TiO2-NPs.
Keywords: Melatonin; TiO2 nanoparticles; Sperm cells velocities; Capoeta trutta; Oxidative stress indices